Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

3. Which equation contains a perfect square trinomial?

A. [tex]x^2 + 14x + 49 = 0[/tex]
B. [tex]x^2 - 5x + 64 = 0[/tex]
C. [tex]x^2 - 6x + 72 = 0[/tex]
D. [tex]x^2 + 2x - 4 = 0[/tex]


Sagot :

To determine which of the given equations contains a perfect square trinomial, we need to understand what a perfect square trinomial is. A quadratic expression [tex]\(ax^2 + bx + c\)[/tex] is a perfect square trinomial if it can be written in the form [tex]\((ax + b)^2\)[/tex]. A common characteristic of a perfect square trinomial is that the constant term [tex]\( c \)[/tex] is a perfect square, and [tex]\( b \)[/tex] is twice the product of [tex]\( a \)[/tex] and the square root of [tex]\( c \)[/tex].

Let's analyze each equation step-by-step:

1. Equation 1: [tex]\(x^2 + 14x + 49 = 0\)[/tex]
We rewrite it as:
[tex]\[ x^2 + 14x + 49 \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = 14\)[/tex], and [tex]\(c = 49\)[/tex].

We check if:
[tex]\[ b^2 = 4ac \][/tex]
[tex]\[ 14^2 = 4 \cdot 1 \cdot 49 \][/tex]
[tex]\[ 196 = 196 \][/tex]
This equation is a perfect square trinomial because it can be factored as:
[tex]\[ (x + 7)^2 = 0 \][/tex]

2. Equation 2: [tex]\(x^2 - 5x + 64 = 0\)[/tex]
We rewrite it as:
[tex]\[ x^2 - 5x + 64 \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = -5\)[/tex], and [tex]\(c = 64\)[/tex].

We check if:
[tex]\[ b^2 = 4ac \][/tex]
[tex]\[ (-5)^2 = 4 \cdot 1 \cdot 64 \][/tex]
[tex]\[ 25 \neq 256 \][/tex]
This equation is not a perfect square trinomial.

3. Equation 3: [tex]\(x^2 - 6x + 72 = 0\)[/tex]
We rewrite it as:
[tex]\[ x^2 - 6x + 72 \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = -6\)[/tex], and [tex]\(c = 72\)[/tex].

We check if:
[tex]\[ b^2 = 4ac \][/tex]
[tex]\[ (-6)^2 = 4 \cdot 1 \cdot 72 \][/tex]
[tex]\[ 36 \neq 288 \][/tex]
This equation is not a perfect square trinomial.

4. Equation 4: [tex]\(x^2 + 2x - 4 = 0\)[/tex]
We rewrite it as:
[tex]\[ x^2 + 2x - 4 \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(c = -4\)[/tex].

We check if:
[tex]\[ b^2 = 4ac \][/tex]
[tex]\[ 2^2 = 4 \cdot 1 \cdot (-4) \][/tex]
[tex]\[ 4 \neq -16 \][/tex]
This equation is not a perfect square trinomial.

Based on these calculations, we find that only the first equation:
[tex]\[ x^2 + 14x + 49 = 0 \][/tex]
contains a perfect square trinomial.

So, the answer is the first equation.